Evaluasi Penilaian Portofolio dan Penilaian Berbasis Kelas SDN Periuk 5 Kota Tangerang - Ina Magdalena; Gerdah Cita Dilla; Hopipah Hapipi; Siti Rahmi Aziah (Jurnal Halaqah, 2020)
The purpose of this paper is to describe the effect of portfolio assessment evaluation and grade-based assessment of SDN Periuk 5 Kota Tangerang. This writing is a descriptive qualitative research in the form of observation sheet through the teacher's fifth-grade interview SDN Peruk 5 Kota Tangerang The results of this study indicate that the teacher SDN Periuk 5 Kota Tangerang has been using portfolio assessment and class-based assessment for a long time in accordance with established procedures. As well as in conducting these assessments the teacher is very more objective in assessing students.